Factors affecting post-operative wound gaping and their outcome in obstetrical and gynecological abdominal surgeries - Narang, Ridhi; Nandmer, Gurpreet K.; Sapkal, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Postoperative wound gaping is a very traumatic event both for patient and treating doctor as it adds economical and psychological burden to the patient and the family. This study was conducted with the aim to find out the various factors affecting postoperative wound gaping and their outcome in obstetrical and gynecological abdominal surgeries. Methods: This Retrospective observational study was carried out in the Department of Obstetrics and Gynecology at Peoples College of medical sciences and research Centre, Bhopal, India from 1st May 2014 to 31st October 2015. Results: A total of 1310 patients underwent major obstetrical and gynecological abdominal surgeries, out of which 29 cases developed postoperative wound gaping with the percentage being 2.2%. The rate was found to be higher among the emergency obstetric case (51.7%). Associated risk factors being anemia (72%), obesity (65%), hypoproteinemia (62%) and diabetes (52%) among gynecological surgeries and prolonged rupture of membranes (53%), emergency LSCS and previous LSCS (47%) among the obstetric cases. The common causative organism was found to be E. coli (28.5%) followed by acinetobacter and pseudomonas. Conclusions: Anemia, obesity, hypoproteinemia, diabetes, history of previous surgeries, emergency operations are the high risk factors for wound gaping in both obstetrics and gynecology surgeries. Correction of anemia, diabetes preoperatively, high protein diet and prevention of other risk factors like avoiding prolonged labor, use potent antibiotics in cases of rupture of membrane, timely intervention, provide well equipped wards with clean environment would be rewarding for better outcome of the surgery.